HAMBATAN KOMUNIKASI INTERPERSONAL PENYULUH AGAMA BUDDHA DALAM MENJELASKAN MODERASI BERAGAMA DI MAMUJU, SULAWESI BARAT - Eko Caram Atandito (Sekolah Tinggi Agama Buddha Negeri Raden Wijaya, 2026)
This study examines interpersonal communication barriers faced by Buddhist religious counselors in conveying religious moderation to Buddhist communities in Mamuju Regency, West Sulawesi. The research is based on the 2025 national policy on religious moderation issued by the Ministry of Religious Affairs of the Republic of Indonesia, which positions religious counselors as strategic actors in promoting moderation values, particularly within minority religious communities. Using a descriptive qualitative approach, data were collected through semi-structured interviews, observation of counseling activities, and analysis of official documents from the Ministry of Religious Affairs of West Sulawesi. Participants included Buddhist religious counselors and members of Buddhist communities involved in religious guidance programs. Data were analyzed using thematic analysis to identify patterns of interpersonal communication barriers. The findings reveal several key obstacles, including limited community understanding of religious moderation as mere tolerance, difficulties in comprehending policy-related terminology, minimal two-way interaction during counseling sessions, and discrepancies between national moderation guidelines and local Buddhist teachings. These barriers hinder the effective internalization of religious moderation values. The study concludes that promoting religious moderation within minority Buddhist communities requires more dialogical, adaptive, and culturally integrated interpersonal communication strategies aligned with Buddhist teachings to ensure meaningful understanding and implementation.